Long-Term Physical Health Outcomes of Resettled Refugee Populations in the United States: A Scoping Review - Kumar, Gayathri S. (J Immigr Minor Health, 2021)
Several studies describe the health of recently resettled refugee populations in the US beyond the first 8 months after arrival. This review summarizes the results of these studies. Scientific articles from five databases published from January 2008 to March 2019 were reviewed. Articles were included if study subjects included any of the top five US resettlement populations during 2008–2018 and if data described long-term physical health outcomes beyond the first 8 months after arrival in the US. Thirty-three studies met the inclusion criteria (1.5%). Refugee adults had higher odds of having a chronic disease compared with non-refugee immigrant adults, and an increased risk for diabetes compared with US-born controls. The most commonly reported chronic diseases among Iraqi, Somali, and Bhutanese refugee adults included diabetes and hypertension. Clinicians should consider screening and evaluating for chronic conditions in the early resettlement period. Further evaluations can build a more comprehensive, long-term health profile of resettled refugees to inform public health practice.